(untitled) (Jurnal Teknologi (Sciences & Engineering), 2023)
In this work, reduced graphene oxide was successfully synthesized from Polyethylene terephthalate (PET) waste in the catalytic reactor. The effects of the production variables such as temperature (375-450 C), weight of bentonite catalyst (1-4%), and holding time (15-60 min) were investigated. The physiochemical properties of reduced graphene oxide were determined by employing various analytical techniques, like X-ray Diffraction (XRD), Fourier Transform Infrared (FTIR), Field Emission Scanning Electron Microscopy (FESEM), Energy-Dispersive X-ray (EDX), and Raman Spectroscopy. Taguchi method was used to investigate the effects of these factors on the production of reduced graphene oxide. Taguchi design methodology was used with an L16 orthogonal system to find the best operating conditions. The results of the experimental analysis showed that the most effective factors in each experimental design response were pyrolysis temperature and holding time. The best-conditions for reduced graphene oxide production from Polyethylene terephthalate (PET) waste were found to be as follows: pyrolysis temperature of 375 °C, the weight of bentonite catalyst 1%, and time of 15 min.